Corporate financial reporting: the challenges in the new millennium / Norasmila Awang and Roshima Said - Awang, Norasmila; Said, Roshima (UiTM Kedah, 2003)
The objective of the paper is to look at several challenges posed by the new information technology towards corporate financial reporting in the era where knowledge assets constitute a larger portion of a firm's worth. The two challenges to corporate financial reporting discussed are the contents of corporate financial reports and the new medium of disseminating the corporate report through the World Wide Web.